2008
DOI: 10.3844/jssp.2008.229.236
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Decision Making Role of Rural Women in Economic Activities: A Comparative Study for Members and Non-Members of the Micro-Credit Organizations in Bangladesh

Abstract: The study was aimed to know the present status of rural women's participation and decision making role in economic activities (called EAs from here) in Bangladesh. The sample of the study consisted of 92 farm women from Rampur village of Palashbari upazila under Gaibandha district. Necessary data for the study were collected with questionnaire by personal interviewing of the respondent women covering all types of farm families (i.e., landless, marginal, small, medium and large). Result showed that among the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 2 publications
7
21
0
1
Order By: Relevance
“…A slightly lower average age of farmers (36 years) has been recorded in other parts of Bangladesh (Hoque and Itohara 2008). The education status of the farmers in this study corresponds with the previous study on rural poultry farmers in Bangladesh (Biswas et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…A slightly lower average age of farmers (36 years) has been recorded in other parts of Bangladesh (Hoque and Itohara 2008). The education status of the farmers in this study corresponds with the previous study on rural poultry farmers in Bangladesh (Biswas et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Studies in Bangladesh have found that apart from economic impact, access to micro-credit has had substantial impact on gender equality. A study by Hoque and Itohara [10] reported that micro-credit is contributing to some extent in generating economic activities and participation in family decision making of the rural women. Another study by Hoque and Itohara [11] also stated that microcredit program in Bangladesh is developing gender awareness among the women.…”
Section: Introductionmentioning
confidence: 99%
“…Their Opinion About Its Contribution: A Study of Gazipur District, Bangladesh processes of the country although they are playing a crucial role in and outside of their home (Hoque and Itohara, 2008). There have been conducted several general studies of contribution of micro-credit on the economic uplift of women and their utilizations.…”
Section: Shaikh Shamim Hasanet Et Al: Women's Involvement In Income mentioning
confidence: 99%